Engineering the Genome of Thermus thermophilus Using a Counterselectable Marker - Carr, Jennifer F. (J Bacteriol, 2015)
Thermus thermophilus is an extremely thermophilic bacterium that is widely used as a model thermophile, in large part due to its amenability to genetic manipulation. Here we describe a system for the introduction of genomic point mutations or deletions using a counterselectable marker consisting of a conditionally lethal mutant allele of pheS encoding the phenylalanyl-tRNA synthetase α-subunit. Mutant PheS with an A294G amino acid substitution renders cells sensitive to the phenylalanine analog p-chlorophenylalanine. Insertion of the mutant pheS allele via a linked kanamycin resistance gene into a chromosomal locus provides a gene replacement intermediate that can be removed by homologous recombination using p-chlorophenylalanine as a counterselective agent. This selection is suitable for the sequential introduction of multiple mutations to produce a final strain unmarked by an antibiotic resistance gene. We demonstrated the utility of this method by constructing strains bearing either a point mutation in or a precise deletion of the rrsB gene encoding 16S rRNA. We also used this selection to identify spontaneous, large-scale deletions in the pTT27 megaplasmid, apparently mediated by either of the T. thermophilus insertion elements ISTth7 and ISTth8. One such deletion removed 121 kb, including 118 genes, or over half of pTT27, including multiple sugar hydrolase genes, and facilitated the development of a plasmid-encoded reporter system based on β-galactosidase. The ability to introduce mutations ranging from single base substitutions to large-scale deletions provides a potentially powerful tool for engineering the genome of T. thermophilus and possibly other thermophiles as well. IMPORTANCE Thermus thermophilus is an extreme thermophile that has played an important part in the development of both biotechnology and basic biological research. Its suitability as a genetic model system is established by its natural competence for transformation, but the scarcity of genetic tools limits the kinds of manipulations that can currently be performed. We have developed a counterselectable marker that allows the introduction of unmarked deletions and point mutations into the T. thermophilus genome. We find that this marker can also be used to select large chromosomal deletions apparently resulting from aberrant transposition of endogenous insertion sequences. This system has the potential to advance the genetic manipulation of this important model organism.